Niger : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2006)
This study focused on the macroeconomic framework, food security needs, implementation of priority investment projects, and domestic petroleum pricing policy. The new fiscal program contains a number of new measures, and it is a precise policy for domestic petroleum pricing. The execution of the revenue mobilization strategy is needed to increase Niger's low revenue-to-gross domestic product (GDP) ratio and to meet the expenditure needs associated with the Millennium Development Goals (MDGs). IMF staff encourages the authorities to activate the pace of structural reforms.